Associations of inclement weather and poor air quality with non-motorized trail volumes. (August 2022) - Acharya, Sailesh; Singleton, Patrick A.
Highlights: Examines associations of air quality and weather with non-motorized counts. Analyzed 32 months of daily count data on two trails in Logan, Utah, US. Area-wide poor air quality decreased trail counts, only at the commuting site. Inclement weather decreased trail counts, more so at the recreational site. An initial step at measuring travel behavior impacts of area-wide air pollution. Abstract: Inclement weather and poor air quality present unfavorable conditions for active transportation. This study investigated associations of area-wide air pollution and inclement weather with non-motorized travel at two trail locations in northern Utah (one recreational, one utilitarian). Rainfall, snowfall, high/low temperatures, and high wind speed were measures of inclement weather, and overall air quality index (AQI) measured air pollution. This study fit time-series (ARIMA) regression models for the utilitarian and recreational sites (separately), using multiple years of daily non-motorized counts. Non-motorized travel was reduced significantly during inclement weather, and the effects of rainfall and cold temperatures were smaller for the utilitarian site than for the recreational site. Counts at the recreational site were higher on holidays, weekends, and days with greater snow depth. Although non-motorized counts were lower on days with worse air quality at the utilitarian location, they were higher at the recreational location. Results are interpreted in terms of the discretionary nature of recreational travel, particulars of the location and elevation of the recreational site, and a desire to escape pollution through outdoor recreation in a natural area.